2011
DOI: 10.4314/ajid.v5i1.66504
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of microscopy compared to molecular diagnosis of <i>P. falciparum</i>: Implications on malaria treatment in epidemic areas in Kenya

Abstract: Detection of Plasmodium species by microscopy has been the gold standard for diagnosis of malaria for more than a century. Despite the fact that there is a significant decline in the number of positive cases reported from microscopy, antimalarial drugs prescriptions are on continuous increase as patients present with symptoms of malaria. This makes it difficult to establish accuracy, sensitivity and specificity of light microscopy in diagnosis of malaria in epidemic areas. This study was designed to compare mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…Similarly, PCR estimated higher prevalence values for the species evaluated and for certain types of co-infection, such increases having been observed in previous studies for both simple and mixed infections [22, 23, 27, 47, 48]. This result highlights PCR’s potential for confirming a clinical suspicion of malaria, in spite of being expensive and not available in health centres having limited resources [61]. This study has thus confirmed the importance of PCR-based diagnosis as the norm in future studies concerning P. malariae epidemiology [19, 36, 48, 53].…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, PCR estimated higher prevalence values for the species evaluated and for certain types of co-infection, such increases having been observed in previous studies for both simple and mixed infections [22, 23, 27, 47, 48]. This result highlights PCR’s potential for confirming a clinical suspicion of malaria, in spite of being expensive and not available in health centres having limited resources [61]. This study has thus confirmed the importance of PCR-based diagnosis as the norm in future studies concerning P. malariae epidemiology [19, 36, 48, 53].…”
Section: Discussionsupporting
confidence: 76%
“…Two studies compared PCR on DBS against liquid whole blood and found a lower sensitivity, particularly for samples with low parasitaemia55,56 (Table 3). DBS PCR compared with microscopy achieves comparable performance or in some studies, is more sensitive 57. However, DBS PCR has a lower sensitivity than PCR on whole blood.…”
Section: Resultsmentioning
confidence: 96%
“…Such diagnostic constraints of microscopy and RDT have serious implications for malaria control in the country. Studies have shown that a missed diagnosis of falciparum malaria increases the risk of complicated or severe disease [ 43 , 44 ]. A missed diagnosis of P. vivax concurrent with P. falciparum is even more problematic since this species could cause relapses, thereby compounding morbidity.…”
Section: Discussionmentioning
confidence: 99%